2017
DOI: 10.1089/cyber.2016.0676
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Video Game Play and ADHD Traits in an Adult Population

Abstract: This study examined the relationship between problematic video game play (PVGP), video game usage, and attention deficit hyperactivity disorder (ADHD) traits in an adult population. A sample of 205 healthy adult volunteers completed the Adult ADHD Self-Report Scale (ASRS), a video game usage questionnaire, and the Problem Video Game Playing Test (PVGT). A significant positive correlation was found between the ASRS and the PVGT. More specifically, inattention symptoms and time spent playing video games were the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
34
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 32 publications
5
34
0
1
Order By: Relevance
“…compared to 14.2 (SD = 5.9) on the hyperactive subscale. These values were similar to those reported in studies using comparable populations 23,32,33 . The two subscales were positively correlated, r = .5, p<.01.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…compared to 14.2 (SD = 5.9) on the hyperactive subscale. These values were similar to those reported in studies using comparable populations 23,32,33 . The two subscales were positively correlated, r = .5, p<.01.…”
Section: Discussionsupporting
confidence: 91%
“…shown that a positive relationship between frequent gaming and ADHD 23,43 . Watching others play video games, on services such as Twitch, and television, on services such as Netflix, was also more frequent among the ADHD group.…”
Section: Accepted Manuscriptmentioning
confidence: 98%
See 1 more Smart Citation
“…Nineteen of the 24 articles included were cross-sectional studies [ 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 ], the rest were two longitudinal studies [ 43 , 44 ], two case-control studies [ 45 , 46 ], and a cohort study [ 47 ]. The research was performed, in descending order, in South Korea (4), Australia (3), Germany (3), Norway (2), Taiwan (2), Canada (1), USA (1), Singapore (1), Spain (1), United Kingdom (1), France (1), Finland (1), Deutschland (1) Austria (1) and Sweden (1).…”
Section: Resultsmentioning
confidence: 99%
“…Mood disorder, anxiety disorders, substance use disorders, personality disorders, learning difficulties, and nicotine dependencies are the most prevalent of these [167][168][169]. Adult ADHD is not only associated with comorbidity and severity of addictions such as substance, gambling, internet, and video gaming, but also with an earlier onset of addiction and poly-dependence [170][171][172]. Although it is possible to identify whether an individual has ADHD or not, accurate identification of ADHD-specific symptoms and clear judgment on ADHD treatment in the light of other comorbid disorders can be challenging [173].…”
Section: Differential Diagnosis and Comorbiditymentioning
confidence: 99%